A brief historical and evolutionary perspective on the origin of cellular microbiology research. (19th July 2019) - Soldati, Thierry; Cardenal‐Muñoz, Elena
Abstract: Integrated with both a historical perspective and an evolutionary angle, this opinion article presents a brief and personal view of the emergence of cellular microbiology research. From the very first observations of phagocytosis by Goeze in 1777 to the exhaustive analysis of the cellular defence mechanisms performed in modern laboratories, the studies by cell biologists and microbiologists have converged into an integrative research field distinct from, but fully coupled to immunity: cellular microbiology. In addition, this brief article is thought as a humble patchwork of the motivations that have guided the research in my group over a quarter century.